Synthesis of two chiral octahydroindole scaffolds for drug discovery. Issue 9 (3rd March 2016) - Sydnes, Magne O.; Van Le, Phuc; Olschimke, Jens; Healy, Peter C.; Garavelas, Agatha; Tajabadi, Fatemeh Mazraati; Pedro, Liliana; Quinn, Ronald J.; Jenkins, Ian D.
Abstract: There are over one thousand natural products that contain the octahydroindole scaffold, which can be considered a biologically validated starting point for the design of compound libraries. Two chiral octahydroindole scaffolds have been synthesized in multigram quantities in two steps from a readily available indoline. They contain either one or two amino groups (one Boc-protected) and a protected carboxylic acid group, and have been designed for ease of conversion to a lead generation library. The structures of both scaffolds have been established unequivocally by single crystal X-ray structure determination. Graphical abstract: Two novel, crystalline, highly functionalized, homochiral scaffolds were efficiently constructed in multigram quantities from readily available starting points.